Analysis of the performance of a fiber optic sensor used to measure the intensity of the electric field - Baghdad Science Journal (مجلة بغداد للعلوم)
In this research was conducted to provide a product to analyze the performance sensor fiber optic used to measure and feel the intensity of the electric field results showed obtained that use sensor long gives reactive high electric field strength and a high value for allergic sensor, but that is at the expense of reducing the intensity of the electric field that is detected